Steel corrosion protection by means of alkyd paints pigmented with calcium acid phosphate - Del Amo, Delia Beatriz (1999)
The use of classic anticorrosive pigments is becoming more and more restricted by increasing environmental concerns; they are gradually being replaced by zinc phosphate and related compounds. Other anticorrosive pigments such as surface-exchanged silicas were also proposed. The object of this research is to study the anticorrosive properties of calcium acid phosphate as an inhibitive pigment, introducing a careful selection of complementary pigments in order to achieve an efficient anticorrosive protection. Several alkyd paints were prepared and evaluated through accelerated and electrochemical tests. The nature of the passive film formed was also studied. Paint containing zinc oxide and calcium carbonate (50/50) as complementary pigments showed the best performance in the salt spray test. Zinc oxide and calcium carbonate decreased film permeability and improved steel passivation. The passive film was composed of ferric oxyhydroxide, the pores of which became plugged by ferric phosphate.